Outage Probability Analysis for Two-Way Amplify-and-Forward Mobile Relay Assisted Device-to-Device Communication in Rayleigh Fading Channel. Issue 1 (1st March 2022) - Wang, Weipeng; Zhao, Jihong; Qu, Hua
Abstract: Device-to-Device (D2D) communication underlaying cellular network is potential to enhance the spectral efficiency, reduce the energy consumption and improve individual quality-of-service (QoS) experience. But intra-cell orthogonality is impaired due to spectral reusing and severe co-channel interference could be imposed between cellular and D2D links. Besides, the direct links between local communicating pairs may be unfavorable and suffer an unsatisfied QoS experience since the randomness of channel condition. So, we are focused on analyzing the outage probability of D2D links assisted by two-way relays on Rayleigh fading channel. Specifically, we consider an amplify-and-forward relay protocol at relay due to their limited processing ability, and devise power control at both D2D transmitter and relay to maintain the QoS requirement of prioritized cellular links. The simulation results verify the correctness of the outage probability analyses for D2D links, and indicate the performance gain when relays are introduced to facilitate D2D links.